PHYSICAL EDUCATION BODY AND SPIRITUALITY IN CONTINUOUS ACTION (Fiep Bulletin - online, 2020)
The commitment of Physical Education is notorious for the competence of Physical Education professionals who identified the body as the center of human movement. In contrast, the world's population has unhealthy health habits because the number of people with risk factors has increased. Overwhelmingly, expositions about the body and spirituality appear against health knowledge in social networks. Sculptural bodies invade the applications, websites, artificial intelligences and social networks. However, virtual tools inform how and what the population needs to know about the body. However, qualified, qualified Physical Education professionals trained to guide; Likewise, able to contribute to continuous actions pertinent to Physical Education, body and spirituality remain inhibited regarding this connection. The article highlights Physical Education as a sustainable nature driving force for body perception and spirituality. He mentions meditation as a practice compatible with the Physical Education course. It elucidates the connection body, spirituality as a competence of Physical Education professionals.